2013
DOI: 10.2174/1567205011310020004
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Rafts Mediate Amyloid-Induced Calcium Dyshomeostasis and Oxidative Stress in Alzheimer’s Disease

Abstract: Several lines of evidence suggest that the initial events of amyloid-p peptide (Ap) oligomerization and deposition in Alzheimer's disease (AD) involve the interaction of soluble oligomers with neuronal membranes. In this study, we show that Ap42 oligomers are recruited to lipid rafts, which are ordered membrane microdomains rich in cholesterol and gangliosides, resulting in lipid peroxidation, Caz* dyshomeostasis and membrane permeabilization in primary fibroblasts from familial AD patients (FAD) bearing APPVa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 1 publication
2
35
0
Order By: Relevance
“…Hippocampal neurons were maintained in neuronal basal medium (NBM) at 37 • C in a 5.0% CO 2 -humidified atmosphere and analyzed 14 days after plating, as previously described [39]. GM1 enrichment was obtained by supplementing neurons with GM1 from bovine brain (150 g/ml) for 24 h at 37 • C, as previously described [40].…”
Section: Cell Culturementioning
confidence: 99%
See 1 more Smart Citation
“…Hippocampal neurons were maintained in neuronal basal medium (NBM) at 37 • C in a 5.0% CO 2 -humidified atmosphere and analyzed 14 days after plating, as previously described [39]. GM1 enrichment was obtained by supplementing neurons with GM1 from bovine brain (150 g/ml) for 24 h at 37 • C, as previously described [40].…”
Section: Cell Culturementioning
confidence: 99%
“…In a separate set of experiments, the cells with increased GM1 content (100 g/ml) were pre-treated for 10 min on ice with 0.05% trypsin and after washing twice treated for 10 or 60 min at 37 • C with A+ or A-oligomers (12 M, monomer equivalents). In another set of experiments the cells with increased GM1 content (100 g/ml) were pre-treated for 60 Primary rat hippocampal neurons with increased GM1 content (150 g/ml) were treated for 60 min with 12 M (monomer equivalents) A␤ 42 oligomers (A+ or A-) in the absence or in the presence of pre-treatment for 20 min with CTX-B, as previously reported [40].…”
Section: Cytosolic Free Ca 2+ Levelsmentioning
confidence: 99%
“…Moreover, the same group has demonstrated that modest depletion of GM1 content decreases the interaction of Aβ oligomers with the plasma membrane in fibroblasts of patients with familial Alzheimer's disease and in rat brain cortical neurons, causing a reduction in cytotoxicity (34).…”
Section: Gm1 In Alzheimer's Disease and Other Amyloid Pathologiesmentioning
confidence: 99%
“…and have been shown to be recruited to lipid rafts (18). ABeta peptide has a high 636 affinity for copper, and Abeta to Abeta--peptide aggregation is stabilized by copper 637 (37).…”
Section: Transmissible Spongiform Encephalopathymentioning
confidence: 99%